Multi-source electricity information fusion methods: A survey - Liu, Kunling; Zeng, Yu; Xu, Jia; Jiang, He; Huang, Yan; Peng, Chengwei (Frontiers in Energy Research, 2023)
With the vigorous development of the global economy, the demand for electricity quality from all walks of life is also increasing, so it is essential to ensure the electric power grid's safe, stable, and efficient operation. Multi-source electric power information fusion, as the core technology of electric power grid data processing, has become the foundation to promote the intelligent and automatic development of the electric power grid. This paper presents the first work on the survey of the methods of electricity information fusion. More precisely, it firstly gives the framework of electricity information fusion methods and shows the types of electricity data. Then, we provide different classifications of existing methods given communication annotation and electric power data, and conduct a thorough comparison and analysis of them. Moreover, we introduce the relevant data sets and evaluation criteria of electric power information, and summarize the corresponding evaluation scenarios. Finally, we conclude our works and provide an outlook to future directions of methods for multi-source electric power information fusion.